PENARIKHAN RADIOKARBON KAITANNNYA DENGAN DINAMIKA DAUR PROSES PENGENDAPAN KUARTER FLUVIAL DAN DANAU TERHADAP PERUBAHAN IKLIM DAN TEKTONIK DI PAPARAN DANAU SINGKARAK, KAB. SOLOK, SUMATERA BARAT - -, Herman Mulyana; -, Herman Moechtar (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
The Quaternary deposits in the studied area comprises of river channel, floodplain, swampy which influence by rising and falling of lake level, lake, tidal-lake, and swamp deposits. These deposited separated by three depositional intervals (IP I-III). Vertically, the character of environment changing seems not gradually. These differences caused by dominant of tectonic effects. Therefore, climate was not important force in controlling the change of the environments. It’s mean, the sedimentary processes on the basin were under controlled by tectonic.